The effect of maxillary premolar distalization with different designed clear aligners: a 4D finite element study with staging simulation - Bochun Mao; Yajing Tian; Dawei Liu; Yanheng Zhou; Shuo Wang (Progress in Orthodontics)
Abstract Background Molar distalization with clear aligners (CAs) is a common treatment. However, when the molars reach their target position and the distal movement of premolars begins, the mesial movement of molars might reduce the overall efficiency of molar distalization. This study aimed to investigate tooth movement patterns under different CA designs in the premolar distalization stage using a four-dimensional mechanical simulation method. Methods A finite element method (FEM) model encompassing the maxillary dentition, periodontal ligaments, attachments, and associated CAs was constructed. The simulation aimed to replicate a premolar distalization of 2 mm within 10 sequential steps. Buccal interradicular mini-implants were used. Three groups of CAs were designed: the conventional CA design group (Con group), the second molar half-wrap group (SMHW group) and the all-molar half-wrap group (MHW group). An iterative computational approach was employed to simulate prolonged tooth movement resulting from orthodontic forces. Additionally, morphological alterations in the CA throughout the staging process were simulated utilizing the thermal expansion method. Results Compared with the Con and SMHW groups, the MHW group presented significantly reduced mesial movement of the first and second molars. However, the MHW group presented the greatest displacement of canines and incisors. The distalization efficiency of premolars in the MHW group reached 95.5–96.5%, which was substantially greater than that in the Con group (84.5–85%) and the SMHW group (75–75.5%). Conclusions The four-dimensional mechanical simulation results indicate that during the process of premolar distalization with CA, removing the distal portion of the aligner covering the first and second molars (MHW group) can effectively reduce the mesial movement of molars. Consequently, this approach can increase the overall efficiency of molar distalization.